An Improved RSA Algorithm for Enhanced Security (Indian Journal of Cryptography and Network Security (IJCNS), 2024)
The security of the Rivest-Shamir-Adelman (RSA) public key algorithm depends on the difficulty of factoring the modulus calculated by multiplying two large prime numbers. The usefulness of the RSA public key algorithm lies in using one key for encryption and another key for decryption. However, a poor choice of the keys used in encryption and decryption can affect the security of the RSA cryptosystem. Many proposals have been made to modify the RSA cryptosystem in such a way that the attacks on the RSA cryptosystem can be overcome. In this article, we propose concealing the publicly disclosed parameters, the encryption key and the common modulus of the RSA cryptosystem by altering the values sent publicly. The values sent publicly are different from the one used in the algorithm which conceals the actual parameters to others. The implementation of this idea uses two different algorithms and randomly choosing between the algorithms. The choice of the algorithm is done using a random number generator and this choice of the algorithm has to be communicated so the decrypt or uses the correct algorithm to decrypt the encrypted data. Finally we explore a faster way to implement the modular exponentiation algorithm used in the RSA encryption and decryption.